(3GdJPcQI GdUaOjIs - (3Ndjd Hf CjHc Hf YHO Gddg GdUaOj , UdGM GdOjf,J (B764 (3g` s
(3ChdgG (B:s
(3hHYOj aEf eOGQS GdYde GdTQja dgG GdPcQ GdNGdO hGdeOQSI GdfGUQjI gi GdhGSWI ai YbhOgG hcGf GdebQ GdcQje bO faV ef jOg YfGfgG aSGA ef HgG ef WdHI GdYde aQGbg s
(3BNQgG (B:s
(3heTjfG Edi GdOcGf aCMVQ di YOI cJH hEPG ajgG Pdc GdcJGH HYjfg aCNPJg hbdJ gh gPG GdcJGH haQMJ s
(3LRA efgGs
(3gfGc Tc ai Cf GdeDda gh fGSN GdeNWhWs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B315 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B114 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B352s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B169 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B388s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs